Phenolic Profile and Antioxidant Activity of Crude Extracts from Microalgae and Cyanobacteria Strains - Idaira Jerez-Martel; Sara García-Poza; Gara Rodríguez-Martel; Milagros Rico; Cristina Afonso-Olivares; Juan Luis Gómez-Pinchetti (Journal of Food Quality)
Aqueous and methanolic extracts of several microalgae (Ankistrodesmus sp., Spirogyra sp., Euglena cantabrica, and Caespitella pascheri) and cyanobacteria (Nostoc sp., Nostoc commune, Nodularia spumigena, Leptolyngbya protospira, Phormidiochaete sp., and Arthrospira platensis) were screened for their radical scavenging activity against the stable radical 1,1-diphenyl-2-picrylhydrazyl. Despite the fact that water was a more efficient solvent to extract greater amount of extractable substances, it seems that methanol was more efficient to extract a selected group of compounds with a higher antioxidant activity. In addition, the identification of 4 simple phenolics (gallic, syringic, protocatechuic, and chlorogenic acids) and the flavonoids (+) catechin and (-) epicatechin was carried out by using reverse phase high performance liquid chromatography. The strain Euglena cantabrica showed the highest concentration of phenolic compounds, particularly gallic and protocatechuic acids (5.87 and 2.97 mg per gram of dried biomass, resp.). Aqueous and methanolic extracts of microalgae Euglena cantabrica also exhibited the highest antioxidant activity, probably due to the presence of the high contents of phenolics.